Treatment of chemical burns using nanoenterosorbent dressings (Experimental biology, 2016)
Today, thanks to advances in science, new opportunities focused and differentiated use of modern dressings properties at various stages of the process of wound healing. In medicine, an improvement dressings led to lower use of the classical version of the dressing. The appearance of the multilayer nonwoven dressings significantly facilitates the work of medical personnel and increases the degree of protection of the wound. In the treatment of burn dressings efficiency due to their sorption properties, anti-infectious abilities, anesthesia and positive influence in their application.Nanoenterosorbents dressings - bandage the new generation, which is designed to provide first aid and wound care with a high risk of infection. Use in wound dressings instead of gauze and cotton wool of other materials, dosage forms and is one of the trends of improvement and the creation of new dressings.
Keywords: chemical burn; dressings nanoenterosorbent; medical.